Bioefficacy of Aegle marmelos extract based amasof-a, a formulated product as fungitoxicant to rice blast pathogen, Pyricularia grisea - and S.N. TEWARI1*, SWAGATIKA ROUT1, H.N. THATOI2 (Indian Phytopathology, 2012)
Amasof-a, an organic product developed by combining a formulating agent (coded Y+) with leaf extract of Aegle marmelos proved effective against Pyricularia grisea, the incitant of rice blast disease. The Product was found to inhibit conidial germination completely at 0.01% and mycelial growth at 0.1% whereas, the extract alone could inhibit the germination only partially at the same concentration. Studies on the shelf-life effect of the product showed retention of fungitoxicity at 0.01% concentration till 12 months storage period but the unformulated extract alone was found ineffective even in a three days period. This formulated product has therefore improved the efficacy of fungitoxicity compared to the unformulated botanical extract, hence possess greater potential for its integration in rice blast control strategy.